(3cJGH GdehVM aj TQM GdJfHjgs - (3YHO GdYRjR Hf YHO GdcQje Hf YHO GdcGai GdLjdi GdgeGeis; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3jHOC HHGH GdTc ai GdWdGb hWdGb GdeQjV s
(3BNQgG (B:s
(3bhdg hEf cGf dQLd CeI aCbQ HhdO efgG hGdCUd HbGA GdQbjI ceG cGfJ gPG BNQ TQM GdJfHjg s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1904s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3Gdabg GdTGaYjs